Instant‐Expertise in Failure Causation: Developing and Presenting a Network of Causes and Recommendations Extracted from Past Failures. Issue 1 (16th August 2018) - Aloisio, Diane; Marais, Karen
Abstract: Systems engineering failures like schedule slips, budget overruns, and other setbacks, occur often and can be costly, but the literature provides little guidance on why these failures occur or how to prevent them. In our previous work we argued that systems engineering failures are manifestations of similar underlying problems, and thus leveraged literature on the theory of accident causation, as well as the many accident investigation reports, to understand better how and why project failures occur and potential ways of preventing these failures. We developed a database of over 900 examples of failure causes and over 600 examples of remedial actions. In this paper, we detail our process for building this database into an interactive network‐based solution aid that anyone experiencing problems in their project or organization can access. The interactive solution aid provides the user with "instant expertise" in accident causation and remediation because it provides users with summaries and simplifications of the causes and remediation measures from the failures we studied.